Enhancing Repurchase Intentions of Sie Reuboh Goreng Aceh Through Brand Image and Product Innovation - Anggi Fitriani; Rizki Amalia (Yayasan Sagita Akademia Maju, 2025)
The study aim to measure the influence of Brand Image and Product Innovation on Repurchase Intention mediated by Customer Satisfaction. Data obtained through a survey from 150 customer as a sample representing the research population using questionnaire as data collection instrument. Statistical Package for the Social Science (SPSS) was used as an analysis tools to determine the influence between the variables involved. The results indicate that Brand Image did not significantly affect Repurchase Intention, while Product Innovation had a significant effect on Repurchase Intention. Brand Image and Product Innovation had a significant effect on Customer Satisfaction. The indirect effect of Customer Satisfaction was able to significantly mediate the effect of Brand Image and Product Innovation on Repurchase Intention.